Designing Active Mats Based on Cellulose Acetate/Polycaprolactone Core/Shell Structures with Different Release Kinetics - Galotto-Lopez, M; Rojas-Sepulveda, A; Lopez de Dicastillo-Bergamo, A; Velasquez, E (Elsevier Ltd, 2021)
Core/shell electrospun mats based on cellulose acetate (CA) and polycaprolactone (PCL) were developed as novel active materials for releasing quercetin (Quer) and curcumin (Cur). The effect of polymeric uniaxial and coaxial electrospun systems and the chemical structures of Quer and Cur on the structural, thermal, and mass transfer properties of the developed mats were investigated. Release modelling indicated that the diffusion of the active agents from the uniaxial PCL fibers was highly dependent on the type of food simulant. Higher diffusion coefficients were obtained for both active agents in acid food simulant due to the higher swelling of the electrospun mats. In addition, CA/PCL coaxial structures slowed down the diffusion of both active agents into both food simulants. CA increased the retention of the active compounds in the polymer structure, resulting in partition coefficients values higher than the values obtained for uniaxial active PCL mats. © 2021 Elsevier Ltd